FORMATION OF CREATIVE EXPERIENCE (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the formation of creative experience. Writers' working styles and their creative approaches are discussed in detail. In fiction, the issue of experience, its age and literary-environmental characteristics, has been comprehensively studied. Reference to the creative works of representatives of Uzbek literature. The thoughts in the article are supported by examples.